Location‐preserved contention‐based routing in vehicular ad hoc networks. Issue 9 (11th April 2014) - Yang, Qing; Lim, Alvin; Ruan, Xiaojun; Qin, Xiao; Kim, Dongjin
Abstract: Location privacy protection in vehicular ad hoc networks considers preserving two types of information: the locations and identifications of users. However, existing solutions, which either replace identifications by pseudonyms or hide locations in areas, cannot be directly applied to geographic routing protocols because they degrade network performance. To address this issue, we proposed a location‐preserved contention (LPC) based routing protocol, in which greedy forwarding is achieved using dummy distance to the destination information instead of users' true locations. Unlike the contention‐based forwarding protocol, the number of duplicated responses in LPC can be reduced by adjusting the parameter α, which is a timer scaling factor. To quantify the efficiency of location privacy protection, an entropy‐based analytical method is proposed. LPC is compared with existing routing and location privacy protection protocols in simulations. Results show that LPC provides 11.7% better network performance and a higher level of location privacy protection than the second best protocol. Copyright © 2014 John Wiley & Sons, Ltd. Abstract : Using pseudonyms and dummy distance to destination information, the proposed location preserved contention based routing protocol can achieve 11.7% improvement on network performance and a higher level of location privacy protection compared with the second best protocol‐contention‐based forwarding active selection.